Identities in Early Medieval Dalmatia - Budak, Neven (2005)
The autheor investigates different sources which reveal data on gentile identity in early medieval dalmatia, and draws conclusions about the relation between more general (Slavic, Roman) and more speciphic identities (Croatian, Dalmatian).